AWS certified security - specialty exam guide all you need to know to clear the aws security speciality exam - Scott, Stuart; Palomar, Wilberto (Packt Publishing, 2020)
Get to grips with the fundamentals of cloud security and prepare for the AWS Security Specialty exam with the help of this comprehensive certification guide Key Features Learn the fundamentals of security with this fast-paced guide Develop modern cloud security skills to build effective security solutions Answer practice questions and take mock tests to pass the exam with confidence Book Description AWS Certified Security - Specialty is a certification exam to validate your expertise in advanced cloud security. With an ever-increasing demand for AWS security skills in the cloud market, this certification can help you advance in your career. This book helps you prepare for the exam and gain certification by guiding you through building complex security solutions. From understanding the AWS shared responsibility model and identity and access management to implementing access management best practices, you'll gradually build on your skills. The book will also delve into securing instances and the principles of securing VPC infrastructure. Covering security threats, vulnerabilities, and attacks such as the DDoS attack, you'll discover how to mitigate these at different layers. You'll then cover compliance and learn how to use AWS to audit and govern infrastructure, as well as to focus on monitoring your environment by implementing logging mechanisms and tracking data. Later, you'll explore how to implement data encryption as you get hands-on with securing a live environment. Finally, you'll discover security best practices that will assist you in making critical decisions relating to cost, security,and deployment complexity. By the end of this AWS security book, you'll have the skills to pass the exam and design secure AWS solutions. What you will learn Understand how to identify and mitigate security incidents Assign appropriate Amazon Web Services (AWS) resources to underpin security requirements Work with the AWS shared responsibility model Secure your AWS public cloud in different layers of cloud computing Discover how to implement authentication through federated and mobile access Monitor and log tasks effectively using AWS Who this book is for If you are a system administrator or a security professional looking to get AWS security certification, this book is for you. Prior experience in securing cloud environments is necessary to get the most out of this AWS book.